# Homework Help

eNotes Homework Help is a way for educators to help students understand their school work. Our experts are here to answer your toughest academic questions! Once it’s posted to our site, your question could help thousands of other students.

### Showing All Questions Answered Popular Recommended Unanswered Editor's Choice in All Subjects Literature History Science Math Arts Business Social Sciences Law and Politics Health Religion Other

• Math
Hello! Consider two intervals: (-1, 0) and (0, 2) to simplify |x|: int_(-1)^2(x-2|x|)dx=int_(-1)^0(x-2|x|)dx+int_0^2(x-2|x|)dx= =int_(-1)^0(x+2x)dx+int_0^2(x-2x)dx=...

Asked by enotes on via web

• Math
You need to find the indefinite integral, hence, you need to remember that sec t = 1/(cos t) , such that: int (sec t)(sec t + tan t) dt = int (1/(cos t))(1 + sin t)/(cos t) dt int (sec t)(sec...

Asked by enotes on via web

• Math
You need to find the indefinite integral, hence, you need to remember that 1 + tan^2 x = 1/(cos^2 x) = (tan x)'. int (1 + tan^2 x )dx = int (tan x)' dx = tan x + c Hence, evaluating the...

Asked by enotes on via web

• Math
You need to find the indefinite integral, hence, you need to remember that sin 2x = 2sin x*cos x , such that: int (sin 2x)(sin x) dx = int (2sin x*cos x)/(sin x) dx  int (sin 2x)(sin x) dx =...

Asked by enotes on via web

• Math
You need to evaluate the integral, hence, you need to use the fundamental theorem of calculus, such that: int_a^b f(x)dx = F(b) - F(a) int_(-2)^3(x^3 - 3)dx = int_(-2)^3(x^3)dx - int_(-2)^3 3...

Asked by enotes on via web

• Math
You need to evaluate the integral, hence, you need to use the fundamental theorem of calculus, such that: int_a^b f(x)dx = F(b) - F(a) int_1^2(4x^3 - 3x^2 + 2x)dx = int_1^2(4x^3)dx - int_1^2...

Asked by enotes on via web

• Math
You need to evaluate the definite integral using the fundamental theorem of calculus, such that: int_a^b f(x)dx = F(b) - F(a) int_(-2)^0 ((1/2)t^4 + (1/4)t^3 - t)dt = int_(-2)^0...

Asked by enotes on via web

• Math
We will use linearity of integral: int(a cdot f(x)+b cdot g(x))dx=a int f(x)dx+b int g(x)dx. int_0^3(1+6w^2-10w^4)dw=int_0^3dw+6int_0^3w^2dw-10int_0^3w^4dw=...

Asked by enotes on via web

• Math
We have to evaluate the integral: \int_{0}^{2}(2x-3)(4x^2+1)dx=\int_{0}^{2}(8x^3-12x^2+2x-3)dx =[8(x^4/4)-12(x^3/3)+2(x^2/2)-3x]_{0}^{2}...

Asked by enotes on via web

• Math
You need to use the following substitution to evaluate the definite integral, such that: 1 - t = u => -dt = du int_(-1)^1 t*(1-t)^2dt = int_(u_1)^(u_2) (1 - u)*u^2 (-du) int_(u_1)^(u_2) (u...

Asked by enotes on via web

• Math
You need to evaluate the definite integral using the fundamental theorem of calculus, such that: int_a^b f(x)dx = F(b) - F(a) int_0^pi (5e^x+ 3sin x)dx = int_0^pi 5e^x dx + int_0^pi 3sin x...

Asked by enotes on via web

• Math
You need to evaluate the definite integral using the fundamental theorem of calculus, such that: int_a^b f(x)dx = F(b) - F(a) int_1^2 (1/x^2 - 4/x^3)dx = int_1^2 1/x^2 dx - int_1^2 4/x^3 dx...

Asked by enotes on via web

• Math
int_1^4(4+6u)/sqrt(u)du =int_1^4(4/sqrt(u)+(6u)/sqrt(u))du =int_1^4(4u^(-1/2)+6u^(1/2))du =[4(u^(-1/2+1)/(-1/2+1))+6(u^(1/2+1)/(1/2+1))]_1^4 =[4(u^(1/2)/(1/2))+6(u^(3/2)/(3/2))]_1^4...

Asked by enotes on via web

• Math
You need to evaluate the definite integral using the fundamental theorem of calculus, such that: int_a^b f(x)dx = F(b) - F(a) int_0^4(3sqrt t - 2e^t)dt = int_0^4 3sqrt tdt - int_0^4 2e^t...

Asked by enotes on via web

• Math
You need to evaluate the definite integral, such that: int_0^1 x(root(3) x + root(4) x)dx = int_0^1 (x^(1+1/3) + x^(1+1/4))dx int_0^1 x(root(3) x + root(4) x)dx = ((x^(2+1/3))/(2+1/3) +...

Asked by enotes on via web

• Math
You need to evaluate the indefinite integral, such that: int f(x)dx = F(x) + c int (x^2 - x^(-2))dx = int (x^2)dx - int x^(-2) dx  Evaluating each definite integral, using the formula int x^n...

Asked by enotes on via web

• Math
int sqrt(x^3)root(3)(x^2) dx Before evaluating, convert the radicals to expressions with rational exponents. = int x^(3/2)*x^(2/3) dx Then, simplify the integrand. Apply the laws of exponent...

Asked by enotes on via web

• Math
int (x^4-1/2x^3+1/4x-2)dx To evaluate this integral, apply the formulas int x^n dx=x^(n+1)/(n+1) +C and int adx = ax + C . int (x^4-1/2x^3+1/4x-2)dx =x^5/5 - 1/2*x^4/4 + 1/4*x^2/2-2x...

Asked by enotes on via web

• Math
int (y^3+1.8y^2-2.4y)dy To evaluate this integral, apply the formula int x^n dx = x^(n+1)/(n+1) + C . = y^4/4 + 1.8y^3/3 - 2.4y^2/2 + C =0.25y^4 + 0.6y^3 - 1.2y^2 + C Therefore, ...

Asked by enotes on via web

• Math
You need to evaluate the indefinite integral, hence, you need to open the brackets, such that: (u+4)(2u+1) = 2u^2 + 9u + 4 int (u+4)(2u+1) du = int (2u^2 + 9u + 4) du  int (u+4)(2u+1) du =...

Asked by enotes on via web

• Math
intv(v^2+2)^2dv =intv((v^2)^2+2v^2*2+2^2)dv =intv(v^4+4v^2+4)dv =int(v^5+4v^3+4v)dv apply the power rule, =v^6/6+4v^4/4+4v^2/2+C , C is constant =v^6/6+v^4+2v^2+C

Asked by enotes on via web

• Math
int(x^3-2sqrt(x))/xdx Simplify by dividing each term in the numerator by x.  <br>  =(x^3/3)-(2x^(1/2))/(1/2)+C =(x^3/3)-4x^(1/2)+C   

Asked by enotes on via web

• Math
int(x^2+1+1/(x^2+1))dx apply the sum rule, =intx^2dx+int1dx+int1/(x^2+1)dx To evaluate the above integrals, we know that, intx^ndx=x^(n+1)/(n+1) and int1/(x^2+1)dx=arctan(x) using above,...

Asked by enotes on via web

• Math
We have to find the integral : \int (sin(x)+sinh(x) )dx=-cos(x)+cosh(x)+C where C is a constant.

Asked by enotes on via web

• Math
int(csc^2(t)-2e^t)dt Apply the sum rule, =intcsc^2(t)dt-int(2e^tdt We now the following common integrals, intcsc^2(x)=-cot(x) and inte^xdx=e^x evaluate using the above, =-cot(t)-2e^t+C...

Asked by enotes on via web

• Math
You need to evaluate the indefinite integral, such that: int f(theta)d theta = F(theta) + c int (theta - csc theta* cot theta)d theta = int theta d theta - int (csc theta* cot theta)d theta...

Asked by enotes on via web

• Math
We have to evaluate the integral and interpret as difference of areas. So, \int_{-1}^{2}x^3dx=[x^4/4]_{-1}^{2} =[(2^4)/4]-1/4 =16/4-1/4 =15/4=3.75 So...

Asked by enotes on via web

• Math
The integral actually represents difference between red area and green area shown in the image below i.e. int_(pi/6)^(2pi)cos(x)dx=P_1-P_2+P_3...

Asked by enotes on via web

• Math
g(x)=int_(2x)^(3x)(u^2-1)/(u^2+1)du g(x)=int_(2x)^0(u^2-1)/(u^2+1)du+int_0^(3x)(u^2-1)/(u^2+1)du g(x)=-int_0^(2x)(u^2-1)/(u^2+1)du+int_0^(3x)(u^2-1)/(u^2+1)du...

Asked by enotes on via web

• Math
Hello! Let's temporarily denote the antiderivative of tsin(t) as A(t). Then the integral is equal to A(1+2x)-A(1-2x) and its derivative is A'(1+2x)*2-A'(1-2x)*(-2)=2*(A'(1+2x)+A'(1-2x))....

Asked by enotes on via web

• Math
F(x)=int_x^(x^2)(e^(t^2))dt From the fundamental theorem of calculus, int_x^(x^2)(e^(t^2))dt=F(x^2)-F(x) d/dxint_x^(x^2)(e^(t^2))dt=F'(x^2).d/dx(x^2)-F'(x) =2x(e^((x^2)^2))-e^(x^2)...

Asked by enotes on via web

• Math
Hello! Let's temporarily denote the antiderivative of arctan(t) as A(t). Then F(x)= A(2x)-A(sqrt(x)), and F'(x)=A'(2x)*2-A'(sqrt(x))*(1/(2sqrt(x))). Recall what A'(x) is and obtain...

Asked by enotes on via web

• Math
You need to evaluate the definite integral using the fundamental theorem of calculus, such that: int_a^b f(u) du = F(b) - F(a) int_0^3 (2sin x - e^x) dx =int_0^3 2sin x dx - int_0^3 e^x dx...

Asked by enotes on via web

• Math
int_1^2((v^3+3v^6)/v^4)dv simplify the integrand and apply the sum rule, =int_1^2(v^3/v^4+(3v^6)/v^4)dv =int_1^2(1/v+3v^2)dv using the following common integrals int1/xdx=ln(x) and...

Asked by enotes on via web

• Math
Evaluate int_1^18(3/z)^(1/2)dz =int_1^18sqrt(3)z^(-1/2)dz =sqrt(3)int_1^18z^(-1/2)dz Integrate the function. =sqrt(3)[z^(1/2)/(1/2)]=sqrt(3)[2z^(1/2)] Evaluate the function from 1 to...

Asked by enotes on via web

• Math
int_0^1 (x^e+e^x)dx To evaluate this, apply the formulas int u^ndu = u^(n+1)/(n+1) and int e^udu=e^u . = (x^(e+1)/(e+1) + e^x) |_0^1 Then, plug-in the limits of integral as follows...

Asked by enotes on via web

• Math
We have to evaluate the integral \int_{0}^{1}cosh(t)dt  We know that the integral of cosh(t) = sinh(t) . Therefore we can write, \int_{0}^{1}cosh(t)dt=[sinh(t)]_{0}^{1}...

Asked by enotes on via web

• Math
You need to evaluate the definite integral using the fundamental theorem of calculus, such that: int_a^b f(x) dx = F(b) - F(a) int_(1/(sqrt3))^(sqrt 3) 8/(1+x^2) dx = 8 int_(1/(sqrt3))^(sqrt 3)...

Asked by enotes on via web

• Math
You need to evaluate the definite integral using the fundamental theorem of calculus, such that: int_a^b f(u) du = F(b) - F(a) int_1^2 (4+u^2)/(u^3) du = int_1^2 4/(u^3) du + int_1^2 (u^2)/(u^3)...

Asked by enotes on via web

• Math
int_(-1)^1 e^(u+1)du To evaluate this, apply the formula int e^x dx = e^x . = e^(u+1) |_(-1)^1 Then, plug-in the limits of the integral as follows F(x) =int_a^b f(x)dx=F(b)-F(a) ....

Asked by enotes on via web

• Math
Hello! This integral is a table one, int((4)/(sqrt(1-x^2)))dx=4arcsin(x)+C. Therefore the definite integral is equal to 4*(arcsin(1/sqrt(2))-arcsin(1/2))=4*(pi/4-pi/6)=4*pi/12=pi/3 approx 1.047.

Asked by enotes on via web

• Math
You need to evaluate the definite integral using the fundamental theorem of calculus such that int_a^b f(x)dx = F(b) - F(a) int_(pi/6)^pi sin theta d theta = -cos theta|_(pi/6)^pi...

Asked by enotes on via web

• Math
Evaluate int_-5^5(e)dx Please note that e is a constant approximately equal to 2.718. Integrate the function. =ex Evaluate the function from x=-5 to x=5. =e(5)-e(-5)=5e+5e=10e =27.183

Asked by enotes on via web

• Math
int_0^1(u+2)(u-3)du =int_0^1(u^2-3u+2u-6)du =int_0^1(u^2-u-6)du =[u^3/3-u^2/2-6u]_0^1 =[1^3/3-1^2/2-6*1]-[0^3/3-0^2/2-6*0] =(1/3-1/2-6) =(2-3-36)/6 =-37/6

Asked by enotes on via web

• Math
Evaluate int_0^4(4-t)(sqrt(t))dt =int_0^4(4t^(1/2)-t^(3/2))dt Integrate the function. inta^n=a^(n+1)/(n+1) =(4t^(3/2))/(3/2)-t^(5/2)/(5/2)=(8/3)t^(3/2)-(2/5)t^(5/2) Evaluate the...

Asked by enotes on via web

• Math
Hello! Find the indefinite integral first: int((x-1)/sqrt(x))dx=int(x^(1/2)-x^(-1/2))dx=(2/3)*x^(3/2)-2*x^(1/2)+C. So the definite integral is equal to...

Asked by enotes on via web

• Math
int_0^2 (y-1)(2y+1)dy Before evaluating, expand the integrand. =int_0^2 (2y^2+y-2y-1)dy =int_0^2(2y^2-y-1)dy Then, apply the integral formulas int x^n dx=x^(n+1)/(n+1) and int cdx = cx ....

Asked by enotes on via web

• Math
int_0^(pi/4) sec^2(t) dt Take note that the derivative of tangent is d/(d theta) tan (theta)= sec^2 (theta). So taking the integral of sec^2(t) result to: = tan (t) |_0^(pi/4) Plug-in the...

Asked by enotes on via web

• Math
int_0^(pi/4) (sec (theta) tan (theta)) d theta Take note that the derivative of secant is d/(d theta) (sec (theta)) = sec(theta) tan (theta) . So taking the integral of sec(theta) tan(theta)...

Asked by enotes on via web

int_1^2(1+2y)^2dy =int_1^2((1)^2+2*2y*1+(2y)^2)dy =int_1^2(1+4y+4y^2)dy =[y+4y^2/2+4y^3/3]_1^2 =[y+2y^2+(4y^3)/3]_1^2 =[2+2(2)^2+(4(2^3))/3]-[1+2(1)^2+(4(1)^3)/3]`...